Prevalence and risk factors of depressive symptoms among 140,259 college students during the COVID-19 epidemic normalization in China: A cross-sectional survey - Luo, Xiaoyu; Xu, Qingqing; Fan, Keliang; Wang, Juan; Wei, Dandan; Wang, Xian; Lou, Xiaomin; Lin, Hualiang; Wang, Chongjian; Wu, Cuiping; Mao, Zhenxing (Frontiers in Public Health, 2022)
Objective: College students are one of the most vulnerable groups of mental health caused by the COVID-19 pandemic. Our study was to investigate the prevalence of depressive symptoms among college students and explored its factors during the coronavirus disease 2019 (COVID-19) epidemic. Methods: A total of 140259 college students were involved from three cities of Henan Province, China, during May 21-27, 2021. Depressive symptoms were determined by the Patient Health Questionnaire-9 (PHQ-9). Odds ratios (ORs) and 95% confidence interval (CIs) for potential factors of depressive symptoms were estimated by using multiple logistic regression analysis. Results: The prevalence of mild depressive symptoms and above among college students is 21.12%. The prevalence of mild depressive symptoms and above was higher in female than in male (61.38% vs. 59.75%) and the prevalence of depressive symptoms was highest among rural students and lowest among city students (21.44% vs. 20.29%). In addition, participants with depressive symptoms more likely to lower behavior status. The proportion of depressive symptoms from none to severe were 78.88%, 15.78%, 2.80%, 1.67% and 0.88%. After adjusting for potential confounders, gender, residential location and behavioral status were found to be associated with depressive symptoms. Conclusion: This cross-sectional study assessed the prevalence of depressive symptoms and its potential influencing factors in college students. These results suggested that governments need to pay more attention to the mental health of college students in combating COVID-19 epidemic normalization.